Türkiye’yi Doğu ve Batı Kavramları Üzerinden Konumlandırmak: Kültürel Kodlar ve Formel Jeopolitik Söylemler - Belçim Öztürk; Nurettin Özgen (Coğrafi Bilimler Dergisi)
This study focuses on how Turkey is positioned between the East and the West through discourses and narratives on the imaginaries of its changing geopolitical trajectory. Specifically, it aims to investigate how the geopolitical and cultural mentality that constructs the concepts of East and West in Turkey creates an East-West imaginary. The debates on East and West in Turkey, while carrying the historical, political and cultural past in their baggage, also have a say in the discourse on current events and phenomena. Although this tendency has changed in some periods, the ontological construction of the depictions of Turkey's geography is mostly based on the construction of East and West. This study was designed according to qualitative research design. The sample group of the study consisted of 240 participants studying at the Faculties of Theology, Literature and Political Sciences/Economic and Administrative Sciences of Istanbul University and Van Yüzüncü Yıl University. The data obtained were analyzed using MAXQDA software. The analyses show that there is a relationship between the way of imagining East and West and geopolitical imaginations subject to political discourse.